Antineutrophil Cytoplasmic Antibody-Associated Vasculitis Update: Genetic Pathogenesis - Li, Weiran; Huang, He; Cai, Minglong; Yuan, Tao; Sheng, Yujun (Frontiers in Immunology, 2021)
Antineutrophil cytoplasmic antibody (ANCA)- associated vasculitis(AAV) is characterized by inflammation of small and medium sized vessels and the presence of proteinase 3 (PR3)-ANCA or myeloperoxidase (MPO)-ANCA in circulation, compromising three clinical subtypes: granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA) and eosinophilic GPA . Although the pathogenesis of AAV is still unclear, genetic factors, environmental factors and immune system are thought to be involved. Among them, genetic factors have been confirmed to play an important role in this disease. Genetic studies including two genome-wide association studies(GWAS) had identified a number of genetic variants in MHC and non-MHC regions associated with AAV. The strongest evidence of MHC association in AAV is with HLA-DP. Significant association between AAV and genetic variations in non MHC regions, such as CTLA-4, FCGR2A, PTPN22, SERPINA1 and TLR9 are also indicated. Moreover, different clinical subtypes of AAV have distinct genetic background. GPA is associated with HLA-DP1, MPA with HLA-DQ and eosinophilic GPA with HLA-DRB4. These findings of genetics of AAV could help to elucidate the aetiology of AAV and to develop new biomarkers for diagnoses and targeted therapy. Herein, we briefly summarize and update the genetic pathogenesis and biomarkers of AAV.